Shortest Route: A Mobile Application for Route Optimization using Digital Map - Oduwole, O. E.; Asaolu, O. S.; Osigbemeh, M. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Businesses that have embarked on using digital maps have been able to increase employee productivity, communicate visually; reduce cost of logistics, planning, resources by more than half of its initial cost. Many industries that have benefitted from this technology include Online Markets, Delivery companies, Agriculture, Real Estate, Engineering, Media, Energy and Utilities, Insurance, Architecture. Seeing this need especially in Nigeria where cost of logistics is high, resources are wasted in the process and productive time is also wasted leading to fatigue and low outcome; there is therefore the need for route optimization for businesses in Nigeria. TSP (Travelling Salesman Problem) - Nearest Neighbour Algorithm is used to solve the problem of route optimization on Google MAP. This study developed a mobile application in Java, HTML and Google SDKs, to find shortest route between various numbers of locations enumerated on digital maps on a smart device. The application was implemented successfully on the Android Operating System for mobile devices. Anyone can download it from the Google play store, install and freely use.